ความแตกต่างของความยืดหยุ่นของหลอดเลือดและการทำงานของเซลล์เอนโดทีเลียมในผู้ป่วยที่มีภาวะสมองขาดเลือดเฉียบพลันและกลุ่มควบคุม - กรรณิการ์ คงบุญเกียรติ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
Background Emerging cardiovascular risk factors such as arterial stiffness and endothelial dysfunction may be important independent predictors of cerebrovascular diseases. No study has evaluated arterial stiffness and endothelial dysfunction in Thai patients with acute lacunar stroke. Methods We enrolled patients diagnosed with acute lacunar stroke admitted to the Internal Medicine Department of the King Chulalongkorn Memorial hospital between July and November 2011. Patients with diabetes or renal disease were excluded. Aged- and gender-matched control subjects without cerebrovascular disease were also studied. Carotid-femoral pulse wave velocity (CF-PWV) as a gold standard measurement of arterial stiffness was measured using SphygmoCor apparatus. Endothelial function was evaluated by reactive hyperemia of peripheral arterial tonometry (RH-PAT) using EndoPAT-2000 system. Results Twenty patients and 20 aged- and gender-matched controls were enrolled. Stroke patients had significant increased in arterial stiffness compared to the controls (CF-PWV 10.4±3.55 m/s vs. 8.7±1.83 m/s, respectively, p = 0.013). In contras, endothelial dysfunction was lower in stroke patients (RHI-PAT of the patients 2.5±0.65 % vs. RHI-PAT of the control 2.0±0.61%, p=0.016). After adjusted for systolic blood pressure, arterial stiffness and endothelial dysfunction was not significantly difference between the groups. Conclusion Our study shows that arterial stiffness and endothelial dysfunction do not increased in Thai patients with acute lacunar stroke compared to aged- and gender-matched controls.